2015
DOI: 10.1002/cplx.21682
|View full text |Cite
|
Sign up to set email alerts
|

Control of non‐integer‐order dynamical systems using sliding mode scheme

Abstract: This article deals with the problem of control of canonical non-integer-order dynamical systems. We design a simple dynamical fractional-order integral sliding manifold with desired stability and convergence properties. The main feature of the proposed dynamical sliding surface is transferring the sign function in the control input to the first derivative of the control signal. Therefore, the resulted control input is smooth and without any discontinuity. So, the harmful chattering, which is an inherent charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…e stability of fractional-order nonlinear systems with 0 < α < 1 was derived in [6,12,13], according to the Lyapunov approach. Based on the uncertain Takagi-Sugeno fuzzy model, the stability problems of nonlinear fractional-order systems were studied, whereas the sidingmode control approach was used to investigate the stabilization and synchronization problems of the nonlinear fractional-order system (e.g., [14][15][16][17][18]). As noted, a growing number of scientists are dedicated to the stability of fractional systems, with most of the above findings concentrating only on nonlinear fractional systems of 0 < α < 1.…”
Section: Introductionmentioning
confidence: 99%
“…e stability of fractional-order nonlinear systems with 0 < α < 1 was derived in [6,12,13], according to the Lyapunov approach. Based on the uncertain Takagi-Sugeno fuzzy model, the stability problems of nonlinear fractional-order systems were studied, whereas the sidingmode control approach was used to investigate the stabilization and synchronization problems of the nonlinear fractional-order system (e.g., [14][15][16][17][18]). As noted, a growing number of scientists are dedicated to the stability of fractional systems, with most of the above findings concentrating only on nonlinear fractional systems of 0 < α < 1.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that fractional‐order non‐linear systems can exhibit unstable, even chaotic, motion under certain conditions [811]. In recent years, the control and synchronisation of fractional‐order non‐linear systems have drawn increasing attention, and many fractional‐order non‐linear control methods have been proposed, including backstepping control [12], pinning control [13], finite time control [14], and extremum seeking control [15].…”
Section: Introductionmentioning
confidence: 99%
“…Synchronization of chaos has also useful applications to biological, chemical, physical systems and secure communications. Furthermore, synchronization and control in chaotic fractional-order dynamical systems have been investigated by authors [30][31][32].…”
Section: Introductionmentioning
confidence: 99%